Mapping the serum proteome to neurological diseases using whole genome sequencing - Png, Grace; Barysenka, Andrei; Repetto, Linda; Navarro, Pau; Shen, Xia; Pietzner, Maik; Wheeler, Eleanor; Wareham, Nicholas J.; Langenberg, Claudia; Tsafantakis, Emmanouil; Karaleftheri, Maria; Dedoussis, George; et al. (Nature communications, 2021)
Despite the increasing global burden of neurological disorders, there is a lack of effective diagnostic and therapeutic biomarkers. Proteins are often dysregulated in disease and have a strong genetic component. Here, we carry out a protein quantitative trait locus analysis of 184 neurologically-relevant proteins, using whole genome sequencing data from two isolated population-based cohorts ( N = 2893). In doing so, we elucidate the genetic landscape of the circulating proteome and its connection to neurological disorders. We detect 214 independently-associated variants for 107 proteins, the majority of which (76%) are cis-acting, including 114 variants that have not been previously identified. Using two-sample Mendelian randomisation, we identify causal associations between serum CD33 and Alzheimer’s disease, GPNMB and Parkinson’s disease, and MSR1 and schizophrenia, describing their clinical potential and highlighting drug repurposing opportunities. Serum proteins are easily accessible biomarkers and drug targets. Here, the authors use whole genome sequencing data to describe the genetic architecture of neurologically-relevant serum proteins and establish causal protein-neurological disease relationships.